Implementation of the digital training concept in the basic flight training in the Serbian Military Academy - Vlačić, Slaviša I.; Knežević, Aleksandar Z.; Grbović, Vladimir M.; Vitsas, Panos A.; Mihajlović, Mihajlo (Mike) S. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The paper provides a review of recent research in the field of digital training applied in the Serbian Military Academy flight training. Flight training represents the foundation of successful education of military pilots. Its division is based on the environment and a phase of realization. The main part and the core of successful flight training is basic flight training. This training phase has experienced significant changes with the introduction of the Technically Advanced aircraft (TAA) which is characterized by a high degree of digitalization not only of the cockpit but also of other aircraft systems. Consequently, a different methodological approach to training is needed, including a digital training concept. The paper shows the achievements and certain solutions based on some elements of digital training concepts used in the basic flight training at the Serbian Military Academy.Methods: The scientific approach is used in the evaluation of aircraft cockpit digitalization and in the implementation of a new training concept in the basic flight training in the Serbian Military Academy.Results: Based on the methodological analysis used, the importance and the values of the digital training concept in basic flight training are shown.Conclusion: Although the digital training concept is not mandatory in the existing flight training model in the Serbian Military Academy, it proves to be a valuable asset. Its potential is significant and, to a certain extent, it can change the nature of basic flight training. Due to digital training, cadets can fly more safely and their flying skills are acquired faster. In accordance with new modern aircraft acquisition in the Serbian Air Force, every aspect of the digital training concept has to be carefully considered, especially in the basic flight training phase, including conversion to new aircraft types.
Keywords: flight training; glass cockpit; digital training; training devices